Second-look arthroscopy after double-bundle posterior cruciate ligament reconstruction: Effect of patient age - Yuta Tachibana; Yoshinari Tanaka; Kinugasa Kazutaka; Shuji Horibe (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2021)
Purpose: Second-look arthroscopy is invasive but still one of the most useful postoperative evaluation methods since graft morphology including graft tension, graft tear, and synovial coverage can be directly evaluated. However, only a few studies have evaluated transplanted posterior cruciate ligament (PCL) grafts. This study aimed to clarify the PCL graft morphology and chondral damages at second-look arthroscopy after double-bundle PCL reconstruction (PCLR) and to investigate the effects of patient age on these arthroscopic findings. Methods: This study retrospectively included 26 patients who underwent second-look arthroscopy at the time of hardware removal 14 months after double-bundle PCLR for isolated PCL injury from January 2007 to December 2020. The patients were divided into two groups: group A, 39 years or younger (n = 14); and group B, 40 years or older (n = 12). At second-look arthroscopy, the grafts were evaluated based on tension (taut, graft tension as tense as a normal PCL; lax, graft tension looser than a normal PCL, unclassified, completely torn graft), tear (one or more tendon strands torn), and synovial coverage (good, synovial coverage greater than 80% around the graft; fair, synovial coverage greater than 50%; and poor, synovial coverage less than 50%). The chondral damages were evaluated using the Outerbridge classification system. Radiographic posterior tibial translation with gravity sag view as well as clinical outcomes were also evaluated. Results: Anterolateral (AL) graft tension was lax in 8% of the patients, whereas posteromedial (PM) graft tension was lax or unclassified in 24% (p = 0.043). Graft tear was observed only in the PM graft of 19% patients (p = 0.022). Synovial coverage of AL grafts was good or fair in all cases, whereas that of PM grafts was poor in 28% cases (p < 0.001). Regarding the effect of patient age, the synovial coverage of PM grafts was significantly poorer in group B (p = 0.033), but no statistical difference in graft tension or tear was found. The chondral damages were significantly advanced in group B (p ≤ 0.01), except for the trochlear groove and lateral femoral condyle. No patients had residual subjective posterior instability, knee swelling, or loss of extension exceeding 5° or flexion exceeding 10°. All patients had improved from grade II or III preoperatively to grade I or grade II in the posterior drawer test. The posterior tibial translation significantly improved from 10.0 ± 3.6 mm preoperatively to 3.6 ± 2.1 mm at second-look arthroscopy. No significant differences in the postoperative clinical outcomes were observed between the two groups. Conclusion: The morphology of the PM grafts at second-look arthroscopy after double-bundle PCLR was poorer than that of the AL grafts. Patient age negatively affected the postoperative graft synovial coverage and chondral status but did not affect the clinical outcomes.